Chemoselectivity control: gold(I)-catalyzed synthesis of 6,7-dihydrobenzofuran-4(5H)-ones and benzofurans from 1-(alkynyl)-7-oxabicyclo[4.1.0]heptan-2-ones - Wang, Tao; Shi, Shuai; Larsen, Mie Højer; Zhang, Tuo; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (Chemistry - a European journal, 2013)
New and chemoselective gold(I)-catalyzed transformations of 1-(arylethynyl)-7-oxabicyclo[4.1.0]- heptan-2-ones were developed. Two completely different products—6,7-dihydrobenzofuran-4(5H)-ones and benzofurans—could be obtained from the same starting material. The selectivity is determined by the ligand of the gold catalyst: triphenylphosphine delivers 6,7-dihydrobenzofuran-4(5H)-ones, and 1,3-bis(diisopropylphenyl)imidazol-2-ylidene leads to benzofurans. Eleven examples of each case are provided. The mechanistic suggestions for the pathways to both product types are supported by isotope labeling experiments.
Gesehen am 30.09.2021